2014
DOI: 10.1155/2014/621384
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Telemedicine in Managing Glycemic Control and Psychobehavioral Aspects of Pregnancy Complicated by Diabetes

Abstract: There is a gradual decline in concern of specialists who follow up the care of pregnant women with diabetes. In addition, due to the dwindling economic resources allocated to health services, access to specialized healthcare facilities is becoming more difficult. Telemedicine, or medicine practiced at a distance, is inserted in this context with applications differing for type of interaction (real-time or deferred, i.e., videoconferencing versus store-and-forward data transmission), type of monitoring (automat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…In this regard, the major aim is to educate patients on healthier lifestyle habits (healthy diet and physical activity domains) [38, 39] and to facilitate the process of illness acceptance [40] after a diagnosis of GDM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, the major aim is to educate patients on healthier lifestyle habits (healthy diet and physical activity domains) [38, 39] and to facilitate the process of illness acceptance [40] after a diagnosis of GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Further research should be conducted to test the effect of integrative programs on QoL focusing on pharmacological care mixed up with advanced practices based on information and communication technologies (e.g., telemedicine and/or games for health) [ 36 , 37 ]. In this regard, the major aim is to educate patients on healthier lifestyle habits (healthy diet and physical activity domains) [ 38 , 39 ] and to facilitate the process of illness acceptance [ 40 ] after a diagnosis of GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Four reviews focused on the use of technologies to evaluate healthy pregnant women in terms of maternal outcomes [ 27 ], women with complicated pregnancies in terms of cost effectiveness [ 28 ], a mixed group of patients (with type 1 DM and GDM) in terms of maternal-neonatal outcomes [ 29 ], and patients with GDM in terms of maternal outcomes [ 30 ]. These studies reported mixed results, did not include ongoing studies without outcomes [ 27 ], lacked systematic searching strategies [ 28 , 29 ], and evaluated limited studies (n=3) [ 30 ]. None of the studies focused on Internet-based self-monitoring approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the research associated with MFM telemedicine programs has been devoted to specific condition management over the course of the pregnancy. [8][9][10][11][12][13][14] In general, there are good levels of acceptance of telemedicine interventions and usage among women. 10,15 However, limited information is available on outcomes associated with MFM care delivered via teleconsult centers compared with an in-person visit.…”
mentioning
confidence: 99%